PUBLIC POLICY PARADOXES ADVANCE THE DEFENSE INDUSTRY - Wahyu Gusriandari; Lukman Yudho Prakoso; Feny Avisha; Ria Anggun Ariani; Sri Sundari; Agus Winarna; Yudi Sutrasna; Sri Murtiana; Juliana Juliana; Gabriel Choirul Alman; M. Ikmal Setiadi; Rianto Rianto (Bajang Institute, 2022)
The onset of the Russian and Ukrainian wars is proof that the existence of physical war is still a real threat to any country at this time. It is common logic that no matter how long our defense and security equipment is still dependent on other countries, we still have limitations in strengthening our country's security defense system. This paper aims to analyze the implementation of policies related to the development of the defense industry to find recommendations in the optimization of the defense industry. The method used is a Literature Study with a descriptive qualitative approach that is the choice and use of George Edward III's policy implementation theory as an operational theory used to analyze problems. The results of the discussion showed that there were still communication constraints between relevant ministries/institutions, limited resources, especially in the priority of using the state budget in other fields, which were the main factors in financing the defense industry. The disposition of relevant ministry/institutional entities that still cannot be fully integrated properly, and also the overlapping authority of the bureaucratic structure. The conclusion of this paper is that the government in this case the President and the House of Representatives of the Republic of Indonesia must firmly decide on priorities to support policies to advance the defense industry that are really realistic to be developed, not stuck with only limited propaganda capable of making their own but the fact is that only separate products from foreign manufacturers